Human respiratory syncytial virus subgroups A and B outbreak in a kindergarten in Zhejiang Province, China, 2023 - Liu, Shelan; Pan, Jinren; Chen, Yin; Ye, Ling; Chen, Enfu; Wen, Xiaosha; Wu, Wenjie; Wu, Bing; Qi, Xiaoqi; Chan, Ta-Chien; Sun, Wanwan; Yu, Zhao; et al. (Frontiers in Public Health, 2024)
Background In May–June 2023, an unprecedented outbreak of human respiratory syncytial virus (HRSV) infections occurred in a kindergarten, Zhejiang Province, China. National, provincial, and local public health officials investigated the cause of the outbreak and instituted actions to control its spread. Methods We interviewed patients with the respiratory symptoms by questionnaire. Respiratory samples were screened for six respiratory pathogens by real-time quantitative polymerase chain reaction (RT-PCR). The confirmed cases were further sequenced of G gene to confirm the HRSV genotype. A phylogenetic tree was reconstructed by maximum likelihood method. Results Of the 103 children in the kindergarten, 45 were classified as suspected cases, and 25 cases were confirmed by RT-PCR. All confirmed cases were identified from half of classes. 36% (9/25) were admitted to hospital, none died. The attack rate was 53.19%. The median ages of suspected and confirmed cases were 32.7 months and 35.8 months, respectively. Nine of 27 confirmed cases lived in one community. Only two-family clusters among 88 household contacts were HRSV positive. A total of 18 of the G gene were obtained from the confirmed cases. Phylogenetic analyses revealed that 16 of the sequences belonged to the HRSV B/BA9 genotype, and the other 2 sequences belonged to the HRSV A/ON1 genotype. The school were closed on June 9 and the outbreak ended on June 15. Conclusion These findings suggest the need for an increased awareness of HRSV coinfections outbreak in the kindergarten, when HRSV resurges in the community after COVID-19 pandemic.